ANALISIS TENTANG MODEL MADZHAB FIQH MUHAMMADIYAH (ANALISIS TENTANG HUKUM ISLAM DALAM PERSPEKTIF KAUM MODERNIS INDONESIA) - Achmad Achmad; Shodiq Abdullah; Akhmad Shodikin; Anne Haerany (IAIN Syekh Nurjati Cirebon, 2022)
The main study in this research is about finding the form and model of the Muhammadiyah school of fiqh. There is a strong assumption that Muhammadiyah has an independent madhhab model of fiqh. However, the manhaj is not out of fiqh ahlu sunnah wal jama'ah. This research model is qualitative, and in its discussion, this research uses descriptive analysis methods, while obtaining data using the library method by looking for books, writings, and journals related to Muhammadiyah, especially about ijtihad. From the results of this study, it was found that the Muhammadiyah fiqh model in its tarjih product was an improved formulation and compilation of the fiqh model used by the previous fiqh schools. From the results of the ijtihad tarjih product, Muhammadiyah has an independent and binding model of fiqh for members of the Muhammadiyah association.Keywords: Tarjih; Modernist; Independent madhhab.